2008
DOI: 10.1099/vir.0.83343-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the genome sequences of non-pathogenic and pathogenic African swine fever virus isolates

Abstract: The genomic coding sequences, apart from the inverted terminal repeats and cross-links, have been determined for two African swine fever virus (ASFV) isolates from the same virus genotype, a non-pathogenic isolate from Portugal, OURT88/3, and a highly pathogenic isolate from West Africa, Benin 97/1. These genome sequences were annotated and compared with that of a tissue culture-adapted isolate, BA71V. The genomes range in length between 170 and 182 kbp and encode between 151 and 157 open reading frames (ORFs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
256
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 257 publications
(285 citation statements)
references
References 49 publications
6
256
0
7
Order By: Relevance
“…2a), thereby confirming their genotype I designation. Similarly, all Nigerian viruses were identical to each other across the 780 bp region spanning the 5'ends of the B125R and B646L (p72) genes, and to other West African genotype I viruses, such as Ben97/1 (Chapman et al 2008) for which homologous data were available (results not shown). In contrast, five size-and sequence-discrete CVR variants were obtained for the Nigerian 2003-6 viruses analysed, corresponding to virus variants containing between 20 and 36 tetrameric repeats (Fig.…”
Section: Phylogenetic Analysesmentioning
confidence: 78%
“…2a), thereby confirming their genotype I designation. Similarly, all Nigerian viruses were identical to each other across the 780 bp region spanning the 5'ends of the B125R and B646L (p72) genes, and to other West African genotype I viruses, such as Ben97/1 (Chapman et al 2008) for which homologous data were available (results not shown). In contrast, five size-and sequence-discrete CVR variants were obtained for the Nigerian 2003-6 viruses analysed, corresponding to virus variants containing between 20 and 36 tetrameric repeats (Fig.…”
Section: Phylogenetic Analysesmentioning
confidence: 78%
“…As referred to above for OURT88/3 (Chapman et al, 2008), NHV is also non-haemadsorbing, with similar deletions as in OURT88/3 for both the lectinlike EP153R and CD2-like EP402R. Haemadsorption is not directly related to virulence, since there are virulent field strains lacking this feature (Gonzague et al, 2001;Pan & Hess, 1984), and deletion of EP402R (8DR) or EP153R (8CR) from Malawi Lil-20/1 did not reduce virulence for domestic pigs, although deletion of 8DR caused a delay in viral spread (Borca et al, 1998;Neilan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Further genomic factors have to be contemplated. Ba71V has an extra deletion of 3.2 kb in the RVR of its genome, resulting in loss of several ORFs conserved in all natural strains of ASFV sequenced to date (Chapman et al, 2008), and also in the present L60 and NHV -I7L, -I8L, -I9R, -I10L and -I11L. These may have an important role for replication in macrophages and/or virulence, but they are still mostly uncharacterized, except for I10L encoding an extra copy of structural viral protein p22, similar to KP177R present in the LVR (Dixon et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations